USM RECEIVES A STUDY VISIT FROM DELEGATION OF KYRGYZSTAN REPUBLIC - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, April 2015 Universiti Sains Malaysia (USM) Centre for Innovation and Productivity in Public Administration (http://pippa.usm.my/index.php/ms/)(PiPPA) recently received a study visit from the delegation of the Republic of Kyrgyzstan at PiPPA seminar room here. The Kyrgyzstan delegation comprised of 11 senior government officials headed by the State Secretary of the Ministry of Finance, Zuura Baiamanova.